Effect of Ethanolic extract of Boerhhvia diffusa against Doxorubicin induced Nephrotoxicity in Albino rats (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Anthracycline derivative i.e. doxorubicin (Dox) has proven efficacy in several malignancies such as breast cancer, Hodgkin and non-Hodgkin lymphoma, acute leukemia, lung, thyroid and ovarian cancer. The clinical usefulness is restricted due to its cardiotoxicity and nephrotoxicity. Boerhaavia diffusa belongs to family Nyctaginaceae and in Ayurveda, it is claimed for use in renal disorders.The main phytoconstituents of the plant are alkaloids, terpenoids, tannins, glycosides, flavonoids, phenolic compounds. To investigate the ameliorative role of ethanolic extract of petals of B. diffusa in doxorubicin-induced nephrotoxicity in rats. Nephrotoxicity was produced by administering doxorubicin (2.5 mg/kg b.w., i.p. alternate day) in six equal injections for two weeks to become cumulatively 15 mg/kg. Low (LEBD–100 mg/kg p.o.)and high (HEBD–200 mg/kg p.o.) dose of ethanolic extract of Boerhhvia diffusa was administered as a pretreatment before doxorubicin administration. The general parameters such as body weight, food, and water intake were measured throughout the study period. Serum markers such as blood urea nitrogen (BUN), serum creatinine and albumin were measured. Antioxidant enzymes such as glutathione (GSH), malondialdehyde (MDA), catalase (CAT), and superoxide dismutase (SOD) were monitored after the last dose. Histopathological studies were also carried out to evaluate nephrotoxicity. The repeated administration of doxorubicin produces several morphological changes, decreased body weight, food, and water consumption. Serum markers such as BUN and serum creatinine were increased and albumin levels decreased. The GSH, SOD, and CAT were decreased, whereas the MDA level was increased, and deteriorating changes in the histological architecture of kidney tissue were observed. The HEBD pretreated groups dose-dependently increased body weight and food and water intake (p < 0.01 and p < 0.05), whereas LEBD does not show any significant changes. The LEBD and HEBD pretreated groups decreased the BUN (p < 0.05 and p < 0.01) and serum creatinine (p < 0.05 and p < 0.05) and increased in the albumin (p < 0.05 and p < 0.05) levels, respectively. The pretreatment with LEBD and HEBD increased the level of the antioxidant enzyme i.e., GSH (p < 0.05 and p < 0.01), SOD (p < 0.05 and p < 0.01), CAT (p < 0.05 and p < 0.01) and decreased the MDA level (p < 0.05 and p < 0.01) respectively. Histopathological studies showed that the pretreatment with LEBD and HEBD groups minimized the tubular damage and reduced the inflammation as compared to doxorubicin-treated group. The biochemical and histopathological results data support the nephroprotective effect of ethanolic extract of B. diffusa, which might be credited to its antioxidant property.